The Fragmented Self In Wintergirls As Seen In Laurie Halse Anderson: A Psychological Analysis - Helmita Helmita; ano ano (Jurnal Ilmiah Pendidikan Scholastic, 2025)
This research analyzes the concept of "fragmented self" in Laurie Halse Anderson's novel Wintergirls, focusing on Lia Overbrook's struggles with anorexia nervosa and bulimia. This issue significantly reflects contemporary mental health challenges exacerbated by social pressures and internal conflicts. The concept of the fragmented self here refers to the disunity or incoherence encompassing an individual's identity, thoughts, and emotions, often manifesting through dissociative conditions, eating disorders, self-harming behaviors, or severe anxiety. The objective of this research is to conduct an in-depth psychological analysis to uncover Lia's self-fragmentation, identify its underlying causes, and understand the psychological consequences she experiences. In this analysis, the researcher utilizes the Freudian psychoanalytic theoretical framework, specifically the concepts of Id, Ego, and Superego. Through applying a descriptive qualitative method by careful textual analysis and literature review, the researcher found that anorexia nervosa is the root of Lia's problems, triggering severe internal conflicts, and this is also reflected in the fragmented writing style of the novel. This research is expected not only to enrich the understanding of psychological concepts within literary contexts but also to raise awareness and empathy towards adolescent mental health issues. Through highlighting Lia's journey, the researcher aims to explain the widespread issue of fragmented identity in contemporary society, providing insights into the psychological basis of such struggles and advocating for greater understanding and support for those facing similar challenges.